Expression Profiling and Clinical Significance of Plasma MicroRNAs in Diabetic Nephropathy. (14th May 2019) - Wang, Jianqin; Wang, Gouqin; Liang, Yaojun; Zhou, Xiaochun
Abstract : Aims . MicroRNAs (miRNAs) stably and abundantly exist in body fluids and have been considered as novel and noninvasive biomarkers for several diseases. The present study is aimed at investigating the expression profiling and clinical significance of plasma miRNAs in the pathogenesis and progression of diabetic nephropathy (DN). Methods . Plasma samples were obtained from 66 DN patients (36 had microalbuminuria and 30 had macroalbuminuria), 36 diabetic patients with normoalbuminuria, and 40 healthy controls. The plasma miRNA profiles were obtained by miRNA low-density array chip and validated by quantitative real-time polymerase chain reaction. The correlations between the differential expression of plasma miRNAs and clinicopathological parameters were explored. Results . miR-150-5p, miR-155-5p, miR-30e, miR-320e, and miR-3196 were found to be differentially expressed in plasma samples among these three groups: diabetic patients with microalbuminuria, diabetic patients with normoalbuminuria, and healthy controls (P < 0.05 ). The expression levels of miR-150-5p and miR-155-5p in patients with macroalbuminuria were 2.3-fold (P = 0.001 ) and 1.5-fold (P = 0.033 ) higher than patients with microalbuminuria, respectively. However, the expression levels of miR-30e, miR-3196, miR-320, and let-7a-5p were not significantly different between these two groups (P > 0.05 ). Furthermore, plasma miR-150-5p (P = 0.016, r = -0.460) and miR-155-5p (P = 0.014, r = -0.467) were negatively correlated with the albuminuria excretion rate, while plasma miR-150-5p (P = 0.01, r = 0.318) and miR-155-5p (P = 0.030, r = 0.271 ) were positively correlated with the estimated glomerular filtration rate. Conclusion . miR-150-5p, miR-155-5p, miR-30e, miR-320e, and miR-3196 are potentially new diagnostic biomarkers for early DN. miR-150-5p and miR-155-5p may be involved in the pathogenesis and progression of DN. Further research is required to verify these findings and clarify the specific molecular mechanisms.